Chronic disruptions of circadian sleep regulation induce specific proinflammatory responses in the rat colon - Polidarová, Lenka; Houdek, Pavel; Sumová, Alena (Chronobiology international, 2017)
Exposure to environmental conditions that disturb the daily rhythms has been shown to enhance the proinflammatory responses of immunostimulant-challenged immune system. However, it is not known whether circadian disturbances may stimulate unchallenged immune responses and thus contribute per se to the development of inflammation-related diseases. Our aim was to ascertain an effect of various conditions threatening the behavioral activity/rest cycle regulation, namely aging with or without melatonin, 6 h advance/delay phase shifts in the light/dark cycle repeated with a 2-day frequency and constant light, on expression of immune markers in the rat colon. The impact of these conditions on parameters of behavioral activity and mRNA levels of selected immune markers in the colonic mucosa of Wistar rats, namely TNFα (Tnf), IL1a (Il1a), IL17RA (Il17ra), STAT3 (Stat3) and Rgs16 (Rsg16), were detected. Our results demonstrate that aging with or without melatonin as well as repeated 6 h advance/delay phase shifts in the light/dark cycle, which increased inactivity as a correlate of sleep during the dark phase of the light/dark cycle (i.e. during the active phase for nocturnal animals), had a minor effect on immune state in the colonic mucosa; all these conditions caused downregulation of gene Rgs16 which is involved in attenuation of the inflammatory response in the colon but did not affect expression of the other immune markers. Interestingly, a long-term absence of melatonin facilitated the aging-induced effect on immune state in the colon. In contrast, exposure to constant light, which perturbed the interval of inactivity (sleep) and led to the complete abolishment of activity/inactivity cycles, activated robustly proinflammatory state in the colon selectively via Stat3-dependent pathway. In spite all these experimental conditions (aging with or without melatonin, shifts in light/dark cycles, constant light) perturbed the activity/rest cycles, none of them induced sleep deprivation. These results provided the first evidence that disruptions in the behavioral activity/inactivity cycles may spontaneously (without immuno-stimulant) induce selective proinflammatory responses in the colonic mucosa. Such effects may take part in the mechanisms of modern lifestyle-induced inflammatory diseases of the gut. ABBREVIATIONS: B2M: β2-microglobulin; DSS: dextran sodium sulfate; Gapdh: glyceraldehyde-3-phosphate dehydrogenase; Ifng: interferon g; Il1a: interleukin 1a; Il1b: interleukin 1b; Il2: interleukin 2; Il6: interleukin 6; Il17ra: interleukin 17 receptor a; LD: light/dark cycle; LL: constant light; LPS: lipopolysaccharide; Mntr1a: melatonin receptor 1a; PINX: pinealectomy; Rgs16: regulator of G protein signaling 16; RT qPCR: quantitative reverse transcription polymerase chain reaction; Stat3: signal transducer and activator of transcription 3; Th17: type 17 T helper cells; Tnfα: tumor necrosis factor α; Tnfrsf1b: tumor necrosis factor receptor superfamily member 1b.
Keywords: Motor Activity; fotoperioda; světlo; Photoperiod; Melatonin; zvířata; Time Factors; Sleep; Animals; časové faktory; pohybová aktivita; potkani Wistar; Circadian Rhythm; Activity Cycles; cirkadiánní rytmus; spánková deprivace; kolon; Colon; cykly aktivity; Rats, Wistar; spánek; Sleep Deprivation; melatonin; Light